2019
DOI: 10.1101/715086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyruvate Kinase M Links Glucose Availability to Protein Synthesis

Abstract: How human cells coordinate various metabolic processes, such as glycolysis and protein translation, remains unclear. One key insight is that various metabolic enzymes have been found to associate with mRNAs, however whether these enzymes regulate mRNA biology in response to changes in cellular metabolic state remains unknown. Here we report that the glycolytic enzyme, pyruvate kinase M (PKM), inhibits the translation of 7% of the transcriptome in response to elevated levels of glucose and pyruvate.Our data sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Recent characterization of the ribosome-associated interactome identified PKM2, LDHA, and ALDOA as being part of a macromolecular complex that controls mRNA location, stability, and translation (Simsek et al, 2017). Enrichment of glycolytic enzymes with ribosomes has been later confirmed, including both spliced isoforms of pyruvate kinase (PKM1 and 2) (Kejiou et al, 2019). Global characterization of the PKM2:RNA interactome has identified hundreds of protein-encoding mRNAs, although the role of PKM2 as modulator of mRNA translation remains far from being clear.…”
Section: The Moonlighting Function Of Glycolytic Enzymes As Rbpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent characterization of the ribosome-associated interactome identified PKM2, LDHA, and ALDOA as being part of a macromolecular complex that controls mRNA location, stability, and translation (Simsek et al, 2017). Enrichment of glycolytic enzymes with ribosomes has been later confirmed, including both spliced isoforms of pyruvate kinase (PKM1 and 2) (Kejiou et al, 2019). Global characterization of the PKM2:RNA interactome has identified hundreds of protein-encoding mRNAs, although the role of PKM2 as modulator of mRNA translation remains far from being clear.…”
Section: The Moonlighting Function Of Glycolytic Enzymes As Rbpsmentioning
confidence: 99%
“…Simsek et al found that PKM2 binds preferentially with ribosomal RNAs and mRNAs associated to the endoplasmic reticulum (ER) promoting the translation of ER and secreted proteins (Simsek et al, 2017). Similarly, Kejiou et al found that PKM2 associates to polysomes in an RNA-dependent manner (Kejiou et al, 2019). However, they did not observe an enrichment of rRNAs associated with PKM2.…”
Section: The Moonlighting Function Of Glycolytic Enzymes As Rbpsmentioning
confidence: 99%
See 1 more Smart Citation
“…But also human PKM was found to associate to ribosomes. In 2019 Kejiou and co-workers discovered that PKM regulates polysome association of mRNAs related to cell cycle (Kejiou et al, 2019). It binds the coding sequence of transcripts with polyacidic stretches and stalls ribosome elongation in human osteosarcoma (U2OS) cells in response to pyruvate and glucose.…”
Section: Pyruvate Kinasementioning
confidence: 99%
“…PKM binding activity and translational regulation is cell cycle-dependent. Binding to ribosomal RNA is also critically discussed by the authors but lacks solid support by their data ( Kejiou et al 2019 ).…”
Section: Pyruvate Kinasementioning
confidence: 99%